(3TQM GdHGdZ GdeOQcs - (3CHh WGdH eMeO Hf GdMSjf Hf eMeO Hf gGQhf Hf GdMSjfs; (3GdMSf Hf GdbGSe Hf EHQGgje Hf ESeGYjd Hf EHQGgje Hf GdMSf Hf GdMSf Hf Ydj Hf CHj WGdHs ((3bGSe Hf MSjf GdgGTei s)
(3ChdgG (B:s
(3GdMeO ddg djf GdYQHjI GdJi fRd HgG GdbQBf HfbSe ai CUhd Gdabg Ydi KdGKI ChLg s
(3BNQgG (B:s
(3dC, Cgd GdLfI ef Gdecdajf gPg UaGJge Je hced hGfJgi TQM GdHGdZ GdeOQc s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3Gdabg GdESdGejs